Lipids as Trans-Acting Effectors for α-Synuclein in the Pathogenesis of Parkinson’s Disease - Ikenaka, Kensuke; Suzuki, Mari; Mochizuki, Hideki; Nagai, Yoshitaka (Frontiers in Neuroscience, 2019)
Aggregation of α-synuclein (αSyn) plays a central role in the pathogenesis of Parkinson’s disease (PD) and dementia with Lewy bodies (DLB). Lewy bodies and Lewy neurites, which consist mainly of aggregated αSyn, are widely observed in the affected regions of patient brains. Except for some familial forms of PD, most sporadic PD patients express the wild-type αSyn protein without any mutations, and the mechanisms as to how wild-type αSyn gains the propensity to pathologically aggregate still remains unclear. Furthermore, the mechanisms by which the same αSyn protein can cause different synucleinopathies with distinct phenotypes and pathologies, such as PD, DLB, and multiple system atrophy, still remain largely unknown. Recently, mutations in the GBA1 gene have been reported be the strongest risk factor for developing sporadic PD. Furthermore, decreased glucocerebrosidase activity has also been reported in the brains of patients with sporadic PD. Moreover, αSyn pathology have also been shown in the brains of lysosomal storage disorder patients, which show glycosphingolipid accumulation. These observations suggest the possibility that altered lipid metabolism and lipid accumulation play roles in αSyn aggregation and PD pathogenesis. Indeed, several previous studies have demonstrated that lipid interactions affect the conformation of αSyn and induces its oligomerization and aggregation. In this review, we will give an overview of the association between αSyn aggregation and lipid interactions from the viewpoints of the etiology, pathology, and genetics of PD. We also discuss the distinct species of αSyn aggregates and their association with specific types of synucleinopathies, and introduce our hypothesis that lipid interactions play a role as trans-acting effectors in producing distinct strains of αSyn fibrils.